2020
DOI: 10.3390/nu12040926
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Combinational Medication of Glycyrrhiza glabra, Agastache rugosa Containing Glycyrrhizic Acid, Tilianin Inhibits Neutrophilic Lung Inflammation by Affecting CXCL2, Interleukin-17/STAT3 Signal Pathways in a Murine Model of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is caused by exposure to toxic particles, such as coal fly ash (CFA), diesel-exhaust particle (DEP), and cigarette smoke (CS), leading to chronic bronchitis, mucus production, and a subsequent lung dysfunction. This study, using a mouse model of COPD, aimed to evaluate the effect of herbal combinational medication of Glycyrrhiza glabra (GG), Agastache rugosa (AR) containing glycyrrhizic acid (GA), and tilianin (TN) as active ingredients. GA, a major active component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 61 publications
0
25
0
1
Order By: Relevance
“…A volume of 100 μl of CFD was administered to each mouse. CFD consists of coal (5 mg/ml), fly ash (10 mg/ml), and diesel exhaust particles (DEP; 5 mg/ml), as previously described (Kim et al, 2020). CFD was intratracheally administered on days 4, 7, and 10.…”
Section: Animal Experiments Regimementioning
confidence: 99%
“…A volume of 100 μl of CFD was administered to each mouse. CFD consists of coal (5 mg/ml), fly ash (10 mg/ml), and diesel exhaust particles (DEP; 5 mg/ml), as previously described (Kim et al, 2020). CFD was intratracheally administered on days 4, 7, and 10.…”
Section: Animal Experiments Regimementioning
confidence: 99%
“…( Ashfaq et al, 2017 , Omar et al, 2012 , Oyama et al, 2016 , Soufy et al, 2012 , Bailly and Vergoten, 2020 , Tong et al, 2020 , Velvizhiv and Annapurani, 2018 , Vispute, 2011 , Wang et al, 2015 , Wu et al, 2019 , Xu et al, 2018 , Zakaryan et al, 2017 , Zhang et al, 2018 , Chen et al, 2017 , Dao et al, 2011 , Editorial 2020 , Hazlett et al, 2019 , Aipire et al, 2020b , Hirabayashi et al, 1991 , Kim et al, 2020 , Lee et al, 2018 , Liu et al, 2019 , Liu et al, 2020 , Long et al, 2013 , Maksoud et al, 2019 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“… Bromhexine a derivative of A. vasica has mucolytic activity In vivo: 400mg/kg p.o. for 8 days in male Wistar rats Increases adhesion of neutrophils to nylon fibers Yastimadhu (Glycyrrhiza glabra) Pitta-anila-asra jith (mitigates pitta-vata-rakta), Shothahara (anti-inflammatory), Ruchya (enhances taste), Rasayana (rejuvenation) a) Antimicrobial b) Immunomodulatory c) Antithrombotic Antitussive, expectorant, antimicrobial, antiviral, anti-oxidant, anti-inflammatory, immune-modulatory activity [ 66 , 122 , [194] , [195] , [196] , [197] ] In vitro: 25-100μg/ml in RAW 264.7 macrophages stimulated with LPS Inhibits LPS-induced TNF-α, IL-1β, IL-6 production In vitro: 50-200μg/ml in LPS-stimulated mouse endometrial epithelial cells Glycyrrhizin inhibits LPS-induced TNF-α, IL-1β, NO & PGE 2 production In vitro: 200, 40, 8mg/l in LPS-induced macrophage cell line of RAW264.7 Glycyrrhizin acid supresses IL-1β, IL-3, IL-5, IL-10, IL-12, IL-13 & TNF- α (LPS stimulated) In vivo: 50 to 100mg/kg p.o. for 11 days in Male BALB/c mice.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, independent studies have shown that above mentioned herbs such as T . chebula [ 52 ] , P. niruri [ 65 ] , V.vinifera [ 55 ], G.glabra [ 66 ], J.adhatoda [ 63 ] and A.sativum [ 67 ] significantly modulated neutrophil functions in disease conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation